2022
DOI: 10.5093/ejpalc2022a10
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Analysis of Emotional Intimate Partner Violence: An Estimation of Dyadic Patterns and Influencing Individual, Family, and Couple Factors

Abstract: Background: The co-occurrence of intimate partner violence (IPV) has been usually determined by co-occurring reports of perpetration and victimization, but still not considering the interdependence of both members' reports. The current research aimed to analyze the dyadic patterns of IPV perpetration and victimization, considering the influence of sexism toward women, family functioning, and relationship duration. Method: The sample involved 242 couples heterosexual couples. The Actor-Partner Interdependence M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…In contrast to previous research comparing the help-seeking behavior of married women to that of unmarried women (see Hu et al, 2021 ; Linos et al, 2014 ; Parvin et al, 2016 ), the present results suggest that women in stable relationships are more likely to report IPV to the police. More stable relationships are also expected to be longer relationships in which the likelihood of confronting conflictive couple situations is higher and IPV is likely to occur more often ( Cooper et al, 2020 ; Juarros-Basterretxea, Ocampo, et al, 2022 ; Kennedy et al, 2018 ; Lafontaine et al, 2020 ; Swiatlo et al, 2020 ). In this regard, the likelihood that women in more stable relationships will seek police help may be related to the larger history of victimization rather than to its severity; this can be considered another way to reach the breaking point, as previously documented in more severe cases ( Peterson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous research comparing the help-seeking behavior of married women to that of unmarried women (see Hu et al, 2021 ; Linos et al, 2014 ; Parvin et al, 2016 ), the present results suggest that women in stable relationships are more likely to report IPV to the police. More stable relationships are also expected to be longer relationships in which the likelihood of confronting conflictive couple situations is higher and IPV is likely to occur more often ( Cooper et al, 2020 ; Juarros-Basterretxea, Ocampo, et al, 2022 ; Kennedy et al, 2018 ; Lafontaine et al, 2020 ; Swiatlo et al, 2020 ). In this regard, the likelihood that women in more stable relationships will seek police help may be related to the larger history of victimization rather than to its severity; this can be considered another way to reach the breaking point, as previously documented in more severe cases ( Peterson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…que podría tener un efecto sobre la satisfacción sexual (Byers & Rehman, 2014). También cabe señalar que en el estudio de ambos miembros de la pareja permitiría un análisis más exhaustivo de los patrones relacionales (Juarros-Basterretxea et al, 2022) y, específicamente, en el análisis de la satisfacción (Byers & MacNeil, 2006;DeLamater & Hyde, 2004), lo que podría aportar evidencias del efecto positivo en la experiencia de satisfacción sexual de un miembro sobre el otro (Fallis et al, 2014) y del impacto del perfil de adhesión del DES de ambos miembros de la pareja.…”
Section: Discussionunclassified
“…Juarros-Basterretxea et al, 2022 ). Within the context of personality, prior research has shown that some traits (such as neuroticism or sadism) can function as risk and protective factors for both actors, victims, and perpetrators (Juarros-Basterretxea et al, 2022 ; Pineda, Martínez-Martínez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 97%
“…The investigation has extended its focus beyond the perpetrators to include an examination of the victims in the context of IPVAW from a dyadic approach (e.g. Juarros-Basterretxea et al, 2022 ). Within the context of personality, prior research has shown that some traits (such as neuroticism or sadism) can function as risk and protective factors for both actors, victims, and perpetrators (Juarros-Basterretxea et al, 2022 ; Pineda, Martínez-Martínez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%